2007
DOI: 10.1177/0269215506070313
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction in individuals with a spinal cord injury and pain

Abstract: Life satisfaction is negatively affected in patients with SCI and pain compared to patients with SCI but without pain. Higher levels of anxiety and depression seem to be predictive for this decreased life satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 28 publications
(27 reference statements)
10
100
0
3
Order By: Relevance
“…19 Findings show that a higher proportion of patients with SCI have more depressed mood than healthy persons. 10 Therefore, the association between depressed mood and pain suggests that the long-term emotional distress experienced by these individuals is significantly influenced by the presence of pain.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19 Findings show that a higher proportion of patients with SCI have more depressed mood than healthy persons. 10 Therefore, the association between depressed mood and pain suggests that the long-term emotional distress experienced by these individuals is significantly influenced by the presence of pain.…”
Section: Discussionmentioning
confidence: 98%
“…10 Therefore, the association between depressed mood and pain suggests that the long-term emotional distress experienced by these individuals is significantly influenced by the presence of pain. 19 However, previous studies were performed using a self-reported questionnaire with various scales about mood and/or they did not have a control group with chronic pain. 10,[19][20][21] In the current face-to-face interview study, we showed that a patient who had chronic pain was more likely to have higher levels of depression.…”
Section: Discussionmentioning
confidence: 99%
“…The differences between the findings may be explained by cultural differences or differences in study population characteristics. The negative impact of pain on life satisfaction has not only been observed in comparisons between patients with CMP and the general population, but also for patients with pain due to stroke [3] or due to spinal cord injury [19,27,30]. Since pain seems a strong predictor of life satisfaction, it is important that all studies of predictors of life satisfaction, regardless of the patients' diagnosis, include pain in their models.…”
Section: Discussionmentioning
confidence: 99%
“…43,56,63,67 Duration: duration assoc w/more hip pain, 66 but not with pain in general or shoulder pain; 48,56,63 one study found a U-shaped curve, with more arm pain o5 years and 420 years after injury and less pain 5-19 years after injury. 65 Course: pain tends to develop months or years after injury; 36,40,45,47,50,55,66,68 once pain develops, it tends to remain stable, 40,48 except for (1) shoulder pain, which shows a tendency to increase over time, 14,66 and (2) Age: rate of PUs assoc w/age in one study (older 4younger), but not others. 67,71,75 Duration: rate of PUS assoc w/duration (o5 years and more than 19 years duration4 5-19 years duration), 49 (20415410 42545 years), 11 (more duration 4less duration), (more than 20 years oless than 20 years duration).…”
Section: Prevalence and Importancementioning
confidence: 97%